An Intramolecular Silylene Borane Capable of Facile Activation of Small Molecules, Including Metal‐Free Dehydrogenation of Water - Mo, Zhenbo; Szilvási, Tibor; Zhou, Yu‐Peng; Yao, Shenglai; Driess, Matthias (Angewandte Chemie, 2017)
The first single‐component N‐heterocyclic silylene borane 1 (LSi‐R‐BMes2; L=PhC(NtBu)2; R=1,12‐xanthendiyl spacer; Mes=2,4,6‐Me3C6H2), acting as a frustrated Lewis pair (FLP) in small‐molecule activation, can be synthesized in 65 % yields. Its HOMO is largely localized at the silicon(II) atom and the LUMO has mainly boron 2p character. In small‐molecule activation 1 allows access to the intramolecular silanone–borane 3 featuring a Si=O→B interaction through reaction with O2, N2O, or CO2, and formation of silanethione borane 4 from reaction with S8. The SiII center in 1 undergoes immediate hydrogenation if exposed to H2 at 1 atm pressure in benzene, affording the silane borane 5‐H2, L(H2)Si‐R‐BMes2. Remarkably, no H2 activation occurs if the single silylene LSiPh and Mes3B intermolecularly separated are exposed to dihydrogen. Unexpectedly, the pre‐organized Si–B separation in 1 enables a metal‐free dehydrogenation of H2O to give the silanone–borane 3 as reactive intermediate. Vereint in einer Komponente aktivieren ein N‐heterocyclisches Silylen und ein Boran eine Reihe kleiner Moleküle, darunter O2, N2O, CO2, H2 und H2O. Durch seine Fähigkeit zur Aktivierung von H2O bietet sich 1 als ein metallfreies System für die Dehydrierung von H2O an.